Badiou and Philosophy - Bowden, Sean (Critical Connections : CRCO, 2021)
GBS_insertPreviewButtonPopup(['ISBN:9780748668342','ISBN:9780748668335','ISBN:9780748643530','ISBN:9780748643523','ISBN:9780748643516']);From Cantor to category/topos theory, from Lacan to Lautman and from Sartre to the subject, these 13 essays engage directly with the work of Alain Badiou. They focus on the philosophical content of Badiou's work and show how he connects both with his contemporaries and his philosophical heritage. This is an important collection for anyone interested in the work of Badiou and contemporary Continental philosophy.